The effects of peer competition-based science learning game on secondary students' performance, achievement goals, and perceived ability. Issue 2 (17th February 2018) - Chen, Ching-Huei; Law, Victor; Chen, Wei-Yu
ABSTRACT: The purpose of this study is to examine the effects of different modes of competition on science learning in a game-based learning (GBL) environment. Some key motivational constructs such as learning goals, performance goals, and perceived ability were also investigated. One hundred ninety-five students from a secondary school in Taiwan were randomly assigned to three conditions (anonymous competition, non-anonymous competition, and a control group) in a GBL environment to learn the concepts of force and balance. The results suggested that students in both the anonymous competition and non-anonymous competition groups outperformed students in the control groups. Additionally, we found that the students in the anonymous competition group reported higher learning goals and higher perceived ability than the control group did, whereas students in the non-anonymous competition group reported higher performance goals than the control group did. This study extends findings from previous research on the influences of GBL on learning and motivation.